Influence of pre-plant root substrate nitrogen levels on growth of selected fruit bearing vegetable seedlings in cylindrical paper pots - Park, Myong Sun; Kim, Hyun Cheul; An, Sewoong; Lee, Chiwon W.; Choi, Jong Myung (Horticulture, environment and biotechnology, 2021)
In raising vegetable seedlings using cylindrical paper pots, the root substrates inside paper pots dry out fast mainly due to air spaces between paper pots created by chinks between the pot’s exterior and the holding tray. Frequent watering is necessary that contributes to the loss of nutrients by leaching during seedling production. This study was carried out to investigate the appropriate concentration of nitrogen required as a pre-planting fertilizer for growing fruit-bearing vegetable seedlings in cylindrical paper pots. For the experiment, the paper pots were made with the root substrate containing perlite (1–3 mm) and peat moss (10-mesh, 10–20% by volume) and they were placed into the 40-cell trays. The concentrations of all essential elements except nitrogen was equal in all treatments and the N concentration was adjusted to 0, 150, 250, 500, and 750 mg L −1 during the substrate formulation. Then, seedling grafts of cucumber, watermelon and tomato were transplanted and seeds of hot pepper were sown directly into the paper pots. The growth of cucumber, watermelon, and tomato plants were measured at 15, 18, and 21 days after transplanting and pepper at 5 weeks after seed sowing. The concentrations of macro-elements, pH, and EC of root substrates were analyzed every week. The pH of root substrates gradually increased during the seedling growth, but the differences in pH among N treatments is not significant. The EC in all treatments did not changed until one week after the transplanting of cucumber, watermelon, and tomato seedling grafts and 3 weeks after seed sowing of pepper. The concentration of Ca remained similar over time during the entire experimental period, but the concentration of Mg and K decreased 3 weeks after the seed sowing for the pepper growing root substrate. The concentrations of Ca, Mg, and K gradually decreased after one week of transplantation (cucumber, watermelon, and tomato). Based on the results, the optimal concentration of N required is 250 mg L −1 for tomato and 500 mg L −1 for cucumber, watermelon, and pepper respectively. In summary, the appropriate N concentration in the root substrate of paper pot is 250–500 mg L −1 , and post-planting fertilization period is 1 week after transplanting for cucumber, watermelon and tomato and 3 weeks after seed sowing for hot pepper.